The possibility of predicting eﬀectiveness oftherapy in patients with new inﬁltrative pulmonary tuberculosis by baseline activity of adenosine deaminase and inﬂammatory response parameters - M. E. Dyakova; N. P. Аlekseeva; D. S. Esmedlyaeva; P. K. Yablonskiy (Туберкулез и болезни лёгких)
The objective: to evaluate the possibility of using the baseline activity of adenosine deaminase (ADA) to predict eﬀectiveness of therapy in patients with new inﬁltrative pulmonary tuberculosis (IPTB).Subjects and Methods. Data of 121 patients with new inﬁltrative pulmonary tuberculosis were analyzed; patients were divided into groups according to therapy eﬀectiveness.Results., The discriminant analysis of data of new inﬁltrative pulmonary tuberculosis patients made it possible to obtain adiscriminant function which included the activity of ADA, the concentration of haptoglobin (HP) and ceruloplasmin (CP) – parameters reﬂecting that severity of the disease and protective potential of the host.Conclusion. Analysis of ADA activity in combination with level of HP and CP allows the following: predicting eﬀectiveness of the intensive phase of therapy before it begins in patients with new inﬁltrative pulmonary tuberculosis (with the accuracy of 77.0%); assuming that the reduction of ADA activity and inhibition of the inﬂammatory response may be useful for treatment of patients with new inﬁltrative pulmonary tuberculosis.